Physicians, colonial racism, and diaspora in West Africa - Patton, Adell, 1936- (University Press of Florida, 1996)
The practice of African medicine is ancient - the source, in fact, of a great deal of Western medical knowledge from the Middle Ages onward. Until the close of the nineteenth century, African and West Indian physicians were able to work freely to protect the health of Africans and Europeans alike in West Africa.